Title THE INFLUENCE OF WORK ENVIRONMENT, COMPENSATION, ORGANIZATIONAL COMMITMENT, MOTIVATION, JOB SATISFACTION ON INDIVIDUAL PERFORMANCE IN COOPERATIVES IN PADANG WEST SUMATRA - Ethika Ethika; Herawati Herawati; Rahmat Hidayat (InFestasi, 2019)
A well-managed cooperative is very useful to improve the welfare of members, which at the same time will have an impact on improving the welfare of the community. Indonesian government always encourages the establishment of cooperatives and their number every year has been increasing, but the ones who perform very well are very few. In general, the problems faced are: not implementing the members’ annual meeting every year, bad credits, poor performance, and dormant. The poor performance of the cooperative cannot be separated from the individual performance of the cooperative concerned, whether it is the board or the managers. Therefore, in this study, the researcher tries to empirically examine several factors that influence the individual performance, using five independent variables, namely: control environment, compensation, organizational commitment, motivation and job satisfaction of managers and cooperative managers. Based on the data processing done by using multiple regression analysis techniques, it is found that the variability of the five variables in influencing the individual performance variable as much as 28.2%, simultaneously (F test) of the five variables significantly influence the individual performance of the cooperative, partial only variable of organizational commitment that significantly influences the individual performance of cooperatives in Padang.